2019
DOI: 10.1016/j.jallcom.2019.02.206
|View full text |Cite
|
Sign up to set email alerts
|

Equations of state of rhodium, iridium and their alloys up to 70 GPa

Abstract: Thermal decomposition of (NH4)2[OsxPt1-xCl6] as single-source precursors for Os-Pt binary alloys has been investigated under ambient and high pressure up to 40 GPa. Thermal decomposition of mixed-metal (NH4)2[OsxPt1-xCl6] precursor in hydrogen atmosphere (reductive environment) under ambient pressure results in formation of β-trans-[Pt(NH3)2Cl2] and α-trans-[Pt(NH3)2Cl2] crystalline intermediates as well as single and twophase Os-Pt binary alloys. For the first time, direct thermal decomposition of coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 64 publications
3
34
0
Order By: Relevance
“…[2,10,13,34] We were able to find the orientation matrices of several grains of the new phase. The [27] first indexing resulted in the orthorhombic lattice parameters (a = 3.8540, b = 4.7106, c = 2.7068 Å) characteristic for marcasite type structure of rhodium pernitride RhN 2. [6,35] However, the detailed analysis of the diffraction pattern revealed several extra features that had to be explained.…”
Section: Resultsmentioning
confidence: 99%
“…[2,10,13,34] We were able to find the orientation matrices of several grains of the new phase. The [27] first indexing resulted in the orthorhombic lattice parameters (a = 3.8540, b = 4.7106, c = 2.7068 Å) characteristic for marcasite type structure of rhodium pernitride RhN 2. [6,35] However, the detailed analysis of the diffraction pattern revealed several extra features that had to be explained.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, single-source precursors strategy has been applied to access high-entropy alloys based on platinum group metals. The strategy requires a synthesis of coordination compounds from water solutions and their further thermal decomposition in a hydrogen flow based on the following principle general scheme [1]: in water solution: a[Ir(NH 3 ) 5 Cl]Cl 2 + b[Rh(NH 3 ) 5 Cl]Cl 2 + (1-a-b)[Ru(NH 3 ) 5 2 O respectively. Details about the synthesis of solid-state precursors and alloys can be found in our earlier publications [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Their low compressibility might be compared only with diamond [2][3][4]. Previously, several binary and multicomponent refractory systems of fccand hcp-structured alloys were investigated under extreme conditions [5][6][7][8]. It has been shown that all known platinum group alloys do not show any temperature and/or pressure induced phase transitions.…”
mentioning
confidence: 99%
See 2 more Smart Citations